The role of self-efficacy in mediating emotional intelligence and work-life balance: a comparative study between pre-pandemic and post-pandemic remote workers in Klang Valley, Malaysia - Safian, Suhaiza; Abdul Rahman, Rozailin; Fontaine, Rodrigue Ancelot Harvey; Ismail, Izhairi (World Academy of Islamic Management (WAIM), 2024)
This research aims to examine the relationship between emotional intelligence and work-life balance mediated by self-efficacy between pre-pandemic and post-pandemic remote workers in Klang Valley, Malaysia. To fill in the gaps, the mediating effect of self-efficacy was analyzed to test this relationship. Primary data was collected through purposive sampling by distributing self-administered questionnaires among 150 pre-pandemic and 150 post-pandemic remote workers as respondents. The study utilized conceptual papers using a hypothesis-based approach. Thus, theories of emotional intelligence proposed by Goleman (1998) through the Emotional Competence Framework were derived as the conceptual framework, and their relationship with work-life balance was examined in this study. In addition, one mediated variable, which is self-efficacy, was also included in this study. The collected data was tested using the Statistical Package for the Social Sciences (SPSS) and Analysis of Moment Structures (AMOS).